DNA barcoding of cyprinids (Labeo rohita, Catla catla and Cirrhinus mrigala), mitochondrial CO1-based study. Issue 1 (2nd January 2019) - Ayesha, Ume Rubab; Shafi, Nuzhat; Akhtar, Tasleem; Zareen, Atiya; Ayub, Huma
Abstract: For DNA barcoding, the Cytochrome C Oxidase 1 gene ( CO1 ) is a genetic marker used as uniform, testimonial authentication and reliable evidence for a universal species-level bio-cataloguing system compared with the morphological identification. The barcoding of Catla catla, Cirrhinus mrigala and Labeo rohita of family Cyprinidae was accomplished in the present study. Amplified CO1 gene through PCR was sequenced and figured out using bioinformatic tools. Conspecific and congeneric, K2P nucleotide deviation and nucleotide composition, the number of haplotypes and haplotype diversity were calculated. All three species of studied fish ( C. catla, L. rohita and C. mrigala ) were G-deficient (17.2, 17.8 and 18.5%) than C (28.3, 27.0, 27.3), A (25.2, 27.3, 26.8) and T (28.0, 28.5, 28.1), respectively. The mean intraspecific and intergeneric K2P genetic distance was .031% and 1.23%, respectively, with a high rate of transitional substitutions. Study revealed that C. catla followed the neutral evolution ( R  = .5), while C. mrigala ( R  = 2.01) and L. rohita ( R  = 2.84) deviated from it and offered very low genetic diversity (<.55).